Accounting for water quality—A framework for agricultural water use - Karimi, Poolad; Chapman, Deborah V.; Valieva, Svetlana; Li, Ruyi; Talbi, Amal (Frontiers in Water, 2024)
Driven by increasing water demand, scarcity concerns, and climate change impacts, numerous countries prioritize solutions for enhanced water use efficiency. However, these solutions often focus primarily on managing water quantities to improve water productivity in agriculture, urban, and industrial sectors. Effective and sustainable water use, however, requires monitoring and management of both water quantity and quality. Traditionally, water quantity and water quality have been managed separately, often by different government agencies with different missions and limited interaction. Ensuring sufficient water quantity for agriculture and food production often takes precedence over managing water quality. Water accounting, as a tool for allocating and managing water quantity is now widely accepted and numerous examples of successful implementation exist worldwide. However, the concept of incorporating water quality into water accounting has not yet been widely promoted. Measuring both quantity and quality in the same water bodies is a fundamental principle of assessment of impacts on water quality, through the determination of loads. The load is the, i.e., amount of a given substance or pollutant for a given period of time. Using the key steps necessary for the development of a water quality monitoring and assessment programme, a framework has been developed that can be applied to water accounting projects using typical water accounting applications. Two examples of potential applications are used to consider the technical, institutional, and financial requirements. Implementing a framework for incorporating water quality monitoring and assessment into water accounting has the potential toshould contribute substantially to the need for more water quality data at global scale. Such data are required to facilitate achievement of Sustainable Development Goal 6 "Ensure availability and sustainable management of water and sanitation for all" through more efficient water resources management and greater awareness of water quality impacts in the agricultural water use sector.